Hollow wall plastic steel winding drainage pipe and manufacturing method thereof

Through the synergy between staged chemical treatment and nanocomposite epoxy coating, a stable interface structure and a multi-layer protection system are formed, which solves the interface failure problem of existing steel-plastic composite drainage pipes under corrosive media, and achieves the effects of high ring stiffness, excellent interface bonding and long-term weather resistance.

CN119910935APending Publication Date: 2025-05-02福建新胜达新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510186540.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing steel-plastic composite drainage pipes are prone to stress corrosion and cracking under the action of wet and corrosive media, resulting in interface failure, and problems such as insufficient ring stiffness, poor water pressure resistance, and weak creep resistance.

Method used

The gradient interface layer is formed by using staged chemical treatment, combining the mechanical interlocking and chemical bonding mechanism of the nanocomposite epoxy coating, a multi-layer protection system is designed, and the process sequence is optimized to form a stable interface structure and long-term protection performance.

Benefits of technology

It significantly enhances the interface bonding strength between metal and polymer materials, improves the load transfer efficiency and anti-permeability barrier effect of composite materials, and extends the service life of drainage pipes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005278671920000141
    Figure BDA0005278671920000141
Patent Text Reader

Abstract

The invention relates to the technical field of pipes, in particular to a hollow wall plastic steel winding drainage pipe and a manufacturing method thereof. The pipe comprises a winding inner pipe, a steel belt winding layer and an outer pipe from inside to outside, wherein the steel belt winding layer adopts a pretreated steel belt subjected to multi-stage modification treatment. A pretreated steel strip is subjected to silicate passivation treatment to form a chemical anchoring bottom layer, gamma-(2, 3-epoxypropoxy) propyltrimethoxysilane coupling treatment is carried out to construct a transition layer, and finally a nano silica sol reinforced epoxy resin composite coating is coated. Through the synergistic effect of chemical anchoring and mechanical interlocking, the ring stiffness of the pipe is greatly improved, and the technical problem of interface failure of a traditional steel-plastic composite pipe is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pipes, and in particular to a hollow-wall plastic-steel wound drainage pipe and a manufacturing method thereof. Background Art

[0002] As an important material for modern municipal engineering, the performance of steel-plastic composite drainage pipes directly affects the safety and service life of urban drainage systems. Traditional steel-plastic composite pipes mostly use simple mechanical compounding or single surface treatment processes, which have technical bottlenecks such as low interface bonding strength and poor environmental adaptability. Under the long-term action of humid and corrosive media, the interface between metal and plastic is prone to stress corrosion cracking, leading to interlayer peeling failure.

[0003] In the prior art, there is a method for modifying the surface of steel strips by phosphate conversion treatment, but the density of the passivation film formed is insufficient and it is difficult to effectively block the penetration of corrosive media; there are also studies that try to use a single silane coupling agent for treatment, but due to the lack of an underlying anchoring structure, the coupling agent molecules are prone to hydrolysis and detachment. In addition, the thermal expansion coefficients of conventional epoxy coatings and steel substrates are quite different, and microcracks are easily generated under temperature alternating conditions, accelerating the process of interface failure. More importantly, the existing production processes often ignore the synergistic effects of various treatment procedures, and the preparation order of different functional layers is unreasonable, resulting in inherent defects in the interface structure. These technical defects have caused the existing steel-plastic composite pipes to generally have problems such as insufficient ring stiffness, poor water pressure resistance, and weak creep resistance, which seriously restricts their application under complex working conditions.

[0004] Therefore, the development of new steel-plastic composite pipe preparation technology with stable interface structure and long-term protective performance has become a technical problem that urgently needs to be overcome in this field. Summary of the invention

[0005] In view of this, the purpose of the present invention is to propose a hollow wall plastic-steel wrapped drainage pipe and a manufacturing method thereof, so as to develop a new type of steel-plastic composite pipe with a stable interface structure and long-term protective performance.

[0006] Based on the above purpose, the present invention provides a hollow wall plastic-steel wrapped drainage pipe, which includes, from inside to outside: a wrapped inner pipe, a steel belt wrapped layer and an outer pipe; the steel belt wrapped layer is obtained by winding a pretreated steel belt around the surface of the wrapped inner pipe.

[0007] Furthermore, the preparation steps of the pretreated steel strip are as follows:

[0008] S1: adding sodium silicate, zinc sulfate, sodium potassium tartrate and sodium dodecylbenzene sulfonate into deionized water, stirring for 20-40 minutes, and adjusting the pH to 3.5-4 with nitric acid to obtain a first impregnation solution;

[0009] S2: adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, glacial acetic acid and ethanol into deionized water and stirring for 20-40 minutes to obtain a second impregnation solution;

[0010] S3: immersing the steel strip in the first impregnation liquid, controlling the temperature of the first impregnation liquid to be 55-65° C., the immersion time to be 8-12 min, and then drying at 75-85° C. for 10-20 h to obtain a primary modified steel strip;

[0011] S4: Immersing the primary modified steel strip in a second impregnation liquid, controlling the temperature of the second impregnation liquid to be 20-30° C., the impregnation time to be 25-35 seconds, then standing in an environment with a humidity of 55%-65% for 10-20 minutes, and then curing at 105-115° C. for 15-25 minutes to obtain a secondary modified steel strip;

[0012] S5: Add epoxy resin E-44, nano-silica sol and polyamide curing agent to a xylene / n-butanol mixed solvent, stir for 20-40 minutes to obtain an epoxy resin coating, and then apply the epoxy resin coating on the surface of the secondary modified steel strip by reverse roller coating process, control the wet film thickness to 80-90μm, and then cure at 75-85℃ for 6-10min, 120-140℃ for 12-18min, and 95-105℃ for 8-12min to obtain a pretreated steel strip.

[0013] Preferably, in step S1, the weight ratio of sodium silicate, zinc sulfate, sodium potassium tartrate, sodium dodecylbenzene sulfonate and deionized water is 10-14:4-5:1-3:0.1-0.15:80-120.

[0014] Preferably, in step S2, the weight ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, glacial acetic acid, ethanol and deionized water is 8-12:0.3-0.6:8-12:50-70.

[0015] Preferably, the steel strip in step S3 is a Q235 steel strip with a thickness of 0.4-0.6 mm.

[0016] Preferably, the amine value of the polyamide curing agent in step S5 is 240 mgKOH / g.

[0017] Preferably, in the step S5, the SiO2 content in the nano-silica sol is 30wt% and the particle size is 20nm.

[0018] Preferably, the volume ratio of xylene to n-butanol in the xylene / n-butanol mixed solvent in step S5 is 7:3.

[0019] Preferably, in step S5, the weight ratio of epoxy resin E-44, nano-silica sol, polyamide curing agent and xylene / n-butanol mixed solvent is 80-120:20-40:30-40:100-140.

[0020] Preferably, the preparation method of the winding inner tube is as follows: high-density polyethylene, pentaerythritol stearate and an antioxidant are melt-extruded at 210-220°C through a twin-screw extruder, and an inner tube blank with a wall thickness of 3.5-4.0 mm and an outer diameter of 700-800 mm is formed through an annular die head, and then cut after water cooling and shaping to obtain an inner tube; the inner tube is placed on a winding machine, the winding angle is adjusted to 45 degrees, the winding machine is started, and the winding speed is set to 0.5-2m / min. During the winding process, hot air is used to fuse the wound pipes during the winding process to obtain a wound inner tube.

[0021] Preferably, the weight ratio of the high-density polyethylene, high-density polyethylene and antioxidant is 75-85:2-4:0.1-1.

[0022] Preferably, the high-density polyethylene has a melt index of 0.3-0.5 g / 10 min at 190° C. and 2.16 kg.

[0023] The present invention further provides a method for manufacturing a hollow-wall plastic-steel wound drainage pipe, comprising the following steps:

[0024] (1) Wrap the pretreated steel strip around the outer wall of the winding inner tube, set the winding angle to 30 degrees, start the winding machine, set the winding speed to 0.4-0.6 m / min, and wind 3 turns to obtain a steel strip wound tube;

[0025] (2) High-density polyethylene, pentaerythritol stearate and antioxidant are melt-extruded at 210-225° C. through a twin-screw extruder, and the extrudate is wrapped on the outer surface of the steel strip winding pipe with a wrapping thickness of 1.8-2.2 mm. The pipe is then cooled and cut to obtain a hollow-wall plastic-steel winding drainage pipe.

[0026] Preferably, in step (2), the weight ratio of high-density polyethylene, pentaerythritol stearate and antioxidant is 75-85:2-4:0.1-1.

[0027] Preferably, in the step (2), the high-density polyethylene has a melt index of 0.08-0.15 g / 10 min at 190° C. and 2.16 kg.

[0028] Beneficial effects of the present invention:

[0029] The present invention achieves multiple technical advantages through innovative surface treatment technology and structural design:

[0030] (1) A gradient interface layer is constructed on the steel substrate surface by using phased chemical treatment, and a stable chemical anchoring structure is formed through the synergistic effect of silicate passivation and silane coupling, which significantly enhances the interfacial bonding strength between metal and polymer materials;

[0031] (2) The network structure formed by the nanocomposite epoxy coating establishes a dual bonding mechanism of mechanical interlocking and chemical bonding at the steel-plastic interface, effectively improving the load transfer efficiency of the composite material;

[0032] (3) The multi-layer protection system forms a continuous and complete anti-permeation barrier through the synergistic protection of the chemical passivation layer, the organic silane transition layer and the dense coating, greatly improving the long-term stability of the pipe in the corrosive medium;

[0033] (4) The optimized process sequence design ensures that each functional layer forms an orderly interface structure, eliminating the problem of interface defect accumulation in traditional processes, and making the material have excellent creep resistance and dimensional stability. This composite reinforcement structure enables the pipe to have high ring stiffness, excellent interface bonding and long-term weather resistance, significantly extending the service life of the drainage pipe. DETAILED DESCRIPTION

[0034] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0035] Embodiment 1:

[0036] (1) 75 kg of high-density polyethylene (190° C., melt index 0.3 g / 10 min at 2.16 kg), 2 kg of pentaerythritol stearate and 0.1 kg of antioxidant 1010 were melt-extruded at 220° C. through a twin-screw extruder, and formed into an inner tube with a wall thickness of 3.5 mm and an outer diameter of 700 mm through an annular die, and then cut after water cooling and shaping to obtain an inner tube;

[0037] (2) placing the inner tube on the winding machine, adjusting the winding angle to 45 degrees, starting the winding machine, setting the winding speed to 0.5 m / min, and using hot air to fuse the wound tube during the winding process to obtain a wound inner tube;

[0038] (3) adding 10 kg of sodium silicate, 4 kg of zinc sulfate, 1 kg of potassium sodium tartrate and 0.1 kg of sodium dodecylbenzene sulfonate to 80 kg of deionized water, stirring for 20 min, and adjusting the pH to 3.5 with nitric acid to obtain a first impregnation solution;

[0039] (4) adding 8 kg of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 0.3 kg of glacial acetic acid and 8 kg of ethanol to 50 kg of deionized water and stirring for 20 minutes to obtain a second impregnation solution;

[0040] (5) immersing a Q235 steel strip having a thickness of 0.5 mm in a first impregnation liquid, controlling the temperature of the first impregnation liquid to be 55° C., the immersion time to be 8 min, and then drying at 75° C. for 20 h to obtain a primary modified steel strip;

[0041] (6) Immersing the primary modified steel strip in a second impregnation liquid, controlling the temperature of the second impregnation liquid to be 20° C., the impregnation time to be 25 seconds, then standing in an environment with a humidity of 55% for 10 minutes, and then curing at 105° C. for 25 minutes to obtain a secondary modified steel strip;

[0042] (7) 80 kg of epoxy resin E-44, 20 kg of nano-silica sol (SiO2 content 30 wt%, particle size 20 nm) and 30 kg of polyamide curing agent (amine value 240 mgKOH / g) were added to 100 kg of xylene / n-butanol (volume ratio 7:3) mixed solvent, stirred for 30 min to obtain epoxy resin coating, and then the epoxy resin coating was coated on the surface of the secondary modified steel strip by reverse roller coating process, the wet film thickness was controlled to 80 μm, and then cured at 75° C. for 6 min, 120° C. for 12 min, and 95° C. for 8 min in sequence to obtain a pretreated steel strip;

[0043] (8) Wrap the pretreated steel strip around the outer wall of the winding inner tube, set the winding angle to 30 degrees, start the winding machine, set the winding speed to 0.4-0.6 m / min, and wrap 3 turns to obtain a steel strip wound tube;

[0044] (9) 75 kg of high-density polyethylene (190°C, melt index 0.08 g / 10 min at 2.16 kg), 2 kg of pentaerythritol stearate and 0.1 kg of antioxidant 1010 were melt-extruded at 210°C through a twin-screw extruder. The extrudate was wrapped on the outer surface of the steel strip wrapped tube with a wrapping thickness of 1.8 mm, and then cooled and cut to obtain a hollow-wall plastic-steel wrapped drainage pipe.

[0045] Embodiment 2:

[0046] (1) 80 kg of high-density polyethylene (190° C., melt index 0.4 g / 10 min at 2.16 kg), 3 kg of pentaerythritol stearate and 0.5 kg of antioxidant 1010 were melt-extruded at 215° C. through a twin-screw extruder, and formed into an inner tube with a wall thickness of 3.8 mm and an outer diameter of 760 mm through an annular die, and then cut after water cooling and shaping to obtain an inner tube;

[0047] (2) placing the inner tube on the winding machine, adjusting the winding angle to 45 degrees, starting the winding machine, setting the winding speed to 1 m / min, and using hot air to fuse the wound tube during the winding process to obtain a wound inner tube;

[0048] (3) adding 12 kg of sodium silicate, 4.5 kg of zinc sulfate, 1.5 kg of potassium sodium tartrate and 0.12 kg of sodium dodecylbenzene sulfonate to 100 kg of deionized water, stirring for 30 min, and adjusting the pH to 3.8 with nitric acid to obtain a first impregnation solution;

[0049] (4) adding 10 kg of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 0.45 kg of glacial acetic acid and 10 kg of ethanol to 60 kg of deionized water and stirring for 30 minutes to obtain a second impregnation solution;

[0050] (5) immersing a Q235 steel strip having a thickness of 0.5 mm in a first impregnation liquid, controlling the temperature of the first impregnation liquid to be 60° C., the immersion time to be 10 min, and then drying at 80° C. for 15 h to obtain a primary modified steel strip;

[0051] (6) Immersing the primary modified steel strip in a second impregnation liquid, controlling the temperature of the second impregnation liquid to be 25° C., the immersion time to be 30 seconds, then standing in an environment with a humidity of 60% for 15 minutes, and then curing at 110° C. for 20 minutes to obtain a secondary modified steel strip;

[0052] (7) 100 kg of epoxy resin E-44, 30 kg of nano-silica sol (SiO2 content 30 wt%, particle size 20 nm) and 35 kg of polyamide curing agent (amine value 240 mgKOH / g) were added to 120 kg of xylene / n-butanol (volume ratio 7:3) mixed solvent, stirred for 30 min to obtain epoxy resin coating, and then the epoxy resin coating was coated on the surface of the secondary modified steel strip by reverse roller coating process, the wet film thickness was controlled to 85 μm, and then cured at 80° C. for 8 min, 130° C. for 15 min, and 100° C. for 10 min in sequence to obtain a pretreated steel strip;

[0053] (8) Wrap the pretreated steel strip around the outer wall of the winding inner tube, set the winding angle to 30 degrees, start the winding machine, set the winding speed to 0.5 m / min, and wrap 3 turns to obtain a steel strip wound tube;

[0054] (9) 80 kg of high-density polyethylene (190°C, melt index 0.1 g / 10 min at 2.16 kg), 3 kg of pentaerythritol stearate and 0.5 kg of antioxidant 1010 were melt-extruded at 220°C through a twin-screw extruder. The extrudate was wrapped on the outer surface of the steel strip wrapped tube with a thickness of 2 mm, and then cooled and cut to obtain a hollow wall plastic steel wrapped drainage pipe.

[0055] Embodiment 3:

[0056] (1) 85 kg of high-density polyethylene (190° C., melt index 0.5 g / 10 min at 2.16 kg), 4 kg of pentaerythritol stearate and 0.1-1 kg of antioxidant 1010 were melt-extruded at 210° C. through a twin-screw extruder, and formed into an inner tube with a wall thickness of 4.0 mm and an outer diameter of 800 mm through an annular die, and then cut after water cooling and shaping to obtain an inner tube;

[0057] (2) placing the inner tube on the winding machine, adjusting the winding angle to 45 degrees, starting the winding machine, setting the winding speed to 2 m / min, and using hot air to fuse the wound tube during the winding process to obtain a wound inner tube;

[0058] (3) adding 14 kg of sodium silicate, 5 kg of zinc sulfate, 3 kg of potassium sodium tartrate and 0.15 kg of sodium dodecylbenzene sulfonate to 120 kg of deionized water, stirring for 40 min, and adjusting the pH to 4 with nitric acid to obtain a first impregnation solution;

[0059] (4) adding 12 kg of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 0.6 kg of glacial acetic acid and 12 kg of ethanol to 70 kg of deionized water and stirring for 40 minutes to obtain a second impregnation solution;

[0060] (5) immersing a Q235 steel strip having a thickness of 0.5 mm in a first impregnation liquid, controlling the temperature of the first impregnation liquid to be 65° C., the immersion time to be 12 min, and then drying at 85° C. for 20 h to obtain a primary modified steel strip;

[0061] (6) Immersing the primary modified steel strip in a second impregnation liquid, controlling the temperature of the second impregnation liquid to be 30° C., the impregnation time to be 35 seconds, then standing in an environment with a humidity of 65% for 20 minutes, and then curing at 115° C. for 15 minutes to obtain a secondary modified steel strip;

[0062] (7) 120 kg of epoxy resin E-44, 40 kg of nano-silica sol (SiO2 content 30 wt%, particle size 20 nm) and 40 kg of polyamide curing agent (amine value 240 mgKOH / g) were added to 140 kg of xylene / n-butanol (volume ratio 7:3) mixed solvent, stirred for 40 min to obtain epoxy resin coating, and then the epoxy resin coating was coated on the surface of the secondary modified steel strip by reverse roller coating process, the wet film thickness was controlled to 90 μm, and then cured at 85° C. for 10 min, 140° C. for 18 min, and 105° C. for 12 min in sequence to obtain a pretreated steel strip;

[0063] (8) Wrap the pretreated steel strip around the outer wall of the winding inner tube, set the winding angle to 30 degrees, start the winding machine, set the winding speed to 0.6 m / min, and wrap 3 turns to obtain a steel strip wound tube;

[0064] (9) Take 75-85 kg of high-density polyethylene (190°C, melt index 0.15 g / 10 min at 2.16 kg), 4 kg of pentaerythritol stearate and 1 kg of antioxidant 1010 and melt extrude them through a twin-screw extruder at 210°C. The extrudate is wrapped on the outer surface of the steel strip wrapped tube with a wrapping thickness of 2.2 mm, and then cooled and cut to obtain a hollow wall plastic steel wrapped drainage pipe.

[0065] Comparative Example 1:

[0066] The difference between Comparative Example 1 and Example 2 is that: the steel strip is not treated with the first impregnation liquid;

[0067] The specific steps are as follows:

[0068] (1) 80 kg of high-density polyethylene (190° C., melt index 0.4 g / 10 min at 2.16 kg), 3 kg of pentaerythritol stearate and 0.5 kg of antioxidant 1010 were melt-extruded at 215° C. through a twin-screw extruder, and formed into an inner tube with a wall thickness of 3.8 mm and an outer diameter of 760 mm through an annular die, and then cut after water cooling and shaping to obtain an inner tube;

[0069] (2) placing the inner tube on the winding machine, adjusting the winding angle to 45 degrees, starting the winding machine, setting the winding speed to 1 m / min, and using hot air to fuse the wound tube during the winding process to obtain a wound inner tube;

[0070] (3) adding 10 kg of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 0.45 kg of glacial acetic acid and 10 kg of ethanol to 60 kg of deionized water and stirring for 30 minutes to obtain a second impregnation solution;

[0071] (4) dipping a Q235 steel strip having a thickness of 0.5 mm in a second dipping solution, controlling the temperature of the second dipping solution to be 25° C. for a dipping time of 30 seconds, then standing in an environment with a humidity of 60% for 15 minutes, and then curing at 110° C. for 20 minutes to obtain a secondary modified steel strip;

[0072] (5) 100 kg of epoxy resin E-44, 30 kg of nano-silica sol (SiO2 content 30 wt%, particle size 20 nm) and 35 kg of polyamide curing agent (amine value 240 mgKOH / g) were added to 120 kg of xylene / n-butanol (volume ratio 7:3) mixed solvent, stirred for 30 min to obtain epoxy resin coating, and then the epoxy resin coating was coated on the surface of the secondary modified steel strip by reverse roller coating process, the wet film thickness was controlled to 85 μm, and then cured at 80° C. for 8 min, 130° C. for 15 min, and 100° C. for 10 min in sequence to obtain a pretreated steel strip;

[0073] (6) Wrap the pretreated steel strip around the outer wall of the winding inner tube, set the winding angle to 30 degrees, start the winding machine, set the winding speed to 0.5 m / min, and wrap 3 turns to obtain a steel strip wound tube;

[0074] (7) 80 kg of high-density polyethylene (190°C, melt index 0.1 g / 10 min at 2.16 kg), 3 kg of pentaerythritol stearate and 0.5 kg of antioxidant 1010 were melt-extruded at 220°C through a twin-screw extruder. The extrudate was wrapped on the outer surface of a steel strip wrapped tube with a thickness of 2 mm, and then cooled and cut to obtain a drainage pipe.

[0075] Comparative Example 2:

[0076] The difference between Comparative Example 2 and Example 2 is that the steel strip is not treated with the second impregnation liquid;

[0077] The specific steps are as follows:

[0078] (1) 80 kg of high-density polyethylene (190° C., melt index 0.4 g / 10 min at 2.16 kg), 3 kg of pentaerythritol stearate and 0.5 kg of antioxidant 1010 were melt-extruded at 215° C. through a twin-screw extruder, and formed into an inner tube with a wall thickness of 3.8 mm and an outer diameter of 760 mm through an annular die, and then cut after water cooling and shaping to obtain an inner tube;

[0079] (2) placing the inner tube on the winding machine, adjusting the winding angle to 45 degrees, starting the winding machine, setting the winding speed to 1 m / min, and using hot air to fuse the wound tube during the winding process to obtain a wound inner tube;

[0080] (3) adding 12 kg of sodium silicate, 4.5 kg of zinc sulfate, 1.5 kg of potassium sodium tartrate and 0.12 kg of sodium dodecylbenzene sulfonate to 100 kg of deionized water, stirring for 30 min, and adjusting the pH to 3.8 with nitric acid to obtain a first impregnation solution;

[0081] (4) immersing a Q235 steel strip having a thickness of 0.5 mm in a first impregnation liquid, controlling the temperature of the first impregnation liquid to be 60° C., the immersion time to be 10 min, and then drying at 80° C. for 15 h to obtain a primary modified steel strip;

[0082] (5) 100 kg of epoxy resin E-44, 30 kg of nano-silica sol (SiO2 content 30 wt%, particle size 20 nm) and 35 kg of polyamide curing agent (amine value 240 mgKOH / g) were added to 120 kg of xylene / n-butanol (volume ratio 7:3) mixed solvent, stirred for 30 min to obtain epoxy resin coating, and then the epoxy resin coating was coated on the surface of the primary modified steel strip by reverse roller coating process, the wet film thickness was controlled to 85 μm, and then cured at 80° C. for 8 min, 130° C. for 15 min, and 100° C. for 10 min in sequence to obtain a pretreated steel strip;

[0083] (6) Wrap the pretreated steel strip around the outer wall of the winding inner tube, set the winding angle to 30 degrees, start the winding machine, set the winding speed to 0.5 m / min, and wrap 3 turns to obtain a steel strip wound tube;

[0084] (7) 80 kg of high-density polyethylene (190°C, melt index 0.1 g / 10 min at 2.16 kg), 3 kg of pentaerythritol stearate and 0.5 kg of antioxidant 1010 were melt-extruded at 220°C through a twin-screw extruder. The extrudate was wrapped on the outer surface of a steel strip wrapped tube with a thickness of 2 mm, and then cooled and cut to obtain a drainage pipe.

[0085] Comparative Example 3:

[0086] The difference between Comparative Example 3 and Example 2 is that: the steel strip is not treated with epoxy resin coating;

[0087] The specific steps are as follows:

[0088] (1) 80 kg of high-density polyethylene (190° C., melt index 0.4 g / 10 min at 2.16 kg), 3 kg of pentaerythritol stearate and 0.5 kg of antioxidant 1010 were melt-extruded at 215° C. through a twin-screw extruder, and formed into an inner tube with a wall thickness of 3.8 mm and an outer diameter of 760 mm through an annular die, and then cut after water cooling and shaping to obtain an inner tube;

[0089] (2) placing the inner tube on the winding machine, adjusting the winding angle to 45 degrees, starting the winding machine, setting the winding speed to 1 m / min, and using hot air to fuse the wound tube during the winding process to obtain a wound inner tube;

[0090] (3) adding 12 kg of sodium silicate, 4.5 kg of zinc sulfate, 1.5 kg of potassium sodium tartrate and 0.12 kg of sodium dodecylbenzene sulfonate to 100 kg of deionized water, stirring for 30 min, and adjusting the pH to 3.8 with nitric acid to obtain a first impregnation solution;

[0091] (4) adding 10 kg of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 0.45 kg of glacial acetic acid and 10 kg of ethanol to 60 kg of deionized water and stirring for 30 minutes to obtain a second impregnation solution;

[0092] (5) immersing a Q235 steel strip having a thickness of 0.5 mm in a first impregnation liquid, controlling the temperature of the first impregnation liquid to be 60° C., the immersion time to be 10 min, and then drying at 80° C. for 15 h to obtain a primary modified steel strip;

[0093] (6) Immersing the primary modified steel strip in a second impregnation liquid, controlling the temperature of the second impregnation liquid to be 25° C., the immersion time to be 30 seconds, then standing in an environment with a humidity of 60% for 15 minutes, and then curing at 110° C. for 20 minutes to obtain a secondary modified steel strip;

[0094] (7) Wrapping the secondary modified steel strip on the outer wall of the winding inner tube, setting the winding angle to 30 degrees, starting the winding machine, setting the winding speed to 0.5 m / min, winding 3 times, and obtaining a steel strip wound tube;

[0095] (8) 80 kg of high-density polyethylene (190°C, melt index 0.1 g / 10 min at 2.16 kg), 3 kg of pentaerythritol stearate and 0.5 kg of antioxidant 1010 were melt-extruded at 220°C through a twin-screw extruder. The extrudate was wrapped on the outer surface of a steel strip wrapped tube with a thickness of 2 mm, and then cooled and cut to obtain a drainage pipe.

[0096] Comparative Example 4:

[0097] The difference between Comparative Example 4 and Example 2 is that the steel strip is first treated with epoxy resin coating, and then treated with the second impregnation liquid and the first impregnation liquid in sequence;

[0098] The specific steps are as follows:

[0099] (1) 80 kg of high-density polyethylene (190° C., melt index 0.4 g / 10 min at 2.16 kg), 3 kg of pentaerythritol stearate and 0.5 kg of antioxidant 1010 were melt-extruded at 215° C. through a twin-screw extruder, and formed into an inner tube with a wall thickness of 3.8 mm and an outer diameter of 760 mm through an annular die, and then cut after water cooling and shaping to obtain an inner tube;

[0100] (2) placing the inner tube on the winding machine, adjusting the winding angle to 45 degrees, starting the winding machine, setting the winding speed to 1 m / min, and using hot air to fuse the wound tube during the winding process to obtain a wound inner tube;

[0101] (3) adding 12 kg of sodium silicate, 4.5 kg of zinc sulfate, 1.5 kg of potassium sodium tartrate and 0.12 kg of sodium dodecylbenzene sulfonate to 100 kg of deionized water, stirring for 30 min, and adjusting the pH to 3.8 with nitric acid to obtain a first impregnation solution;

[0102] (4) adding 10 kg of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 0.45 kg of glacial acetic acid and 10 kg of ethanol to 60 kg of deionized water and stirring for 30 minutes to obtain a second impregnation solution;

[0103] (5) 100 kg of epoxy resin E-44, 30 kg of nano-silica sol (SiO2 content 30 wt%, particle size 20 nm) and 35 kg of polyamide curing agent (amine value 240 mgKOH / g) were added to 120 kg of xylene / n-butanol (volume ratio 7:3) mixed solvent, stirred for 30 min to obtain epoxy resin coating, and then the epoxy resin coating was coated on the surface of Q235 steel strip with a thickness of 0.5 mm by reverse roller coating process, and the wet film thickness was controlled to 85 μm, and then cured at 80° C. for 8 min, 130° C. for 15 min, and 100° C. for 10 min in sequence to obtain a pretreated steel strip;

[0104] (6) immersing the pretreated steel strip in a second impregnation liquid, controlling the temperature of the second impregnation liquid to be 60° C., the immersion time to be 10 min, and then drying at 80° C. for 15 h to obtain a secondary modified steel strip;

[0105] (7) Immersing the secondary modified steel strip in the first impregnation liquid, controlling the temperature of the first impregnation liquid to be 25° C., the immersion time to be 30 seconds, then standing for 15 minutes in an environment with a humidity of 60%, and then curing at 110° C. for 20 minutes to obtain a primary modified steel strip;

[0106] (8) Wrap the modified steel strip once on the outer wall of the winding inner tube, set the winding angle to 30 degrees, start the winding machine, set the winding speed to 0.5 m / min, and wrap 3 turns to obtain a steel strip wound tube;

[0107] (9) 80 kg of high-density polyethylene (190°C, melt index 0.1 g / 10 min at 2.16 kg), 3 kg of pentaerythritol stearate and 0.5 kg of antioxidant 1010 were melt-extruded at 220°C through a twin-screw extruder. The extrudate was wrapped on the outer surface of a steel strip winding tube with a wrapping thickness of 2 mm, and then cooled and cut to obtain a drainage pipe.

[0108] Performance Test:

[0109] Ring stiffness test: refer to standard GB / T 9647-2015, prepare according to standard specimen, and test the load value when the radial deformation of the pipe is 3% by three-point method. The results are shown in Table 1.

[0110] Peel strength: Referring to the standard GB / T 2791-1995, a 180° peel test was adopted with a tensile speed of (50±5) mm / min to detect the bonding strength between the steel strip and the outer layer. The results are shown in Table 1.

[0111] Long-term creep performance: 0.4MPa ring stress was applied at 80℃, and the rupture time of the pipe was recorded. The results are shown in Table 1.

[0112] Water pressure resistance: 0.6MPa hydrostatic pressure was maintained for 24h, and the leakage of the pipe was observed. The results are shown in Table 1.

[0113] Chemical resistance: After immersion in 10% H2SO4 solution for 30 days, the mass change rate was measured. The results are shown in Table 1.

[0114] Table 1 Performance test results

[0115]

[0116] Data Analysis:

[0117] From the data of Examples 1-3 in Table 1, it can be seen that the three-dimensional composite structure formed by the dual interface modification and gradient curing process of the present invention has a higher ring stiffness indicating that the material has excellent deformation resistance. The longer creep rupture time reveals that the pipe containing pretreated steel has higher stability. The extremely low mass change rate confirms the chemical stability of the pipe containing pretreated steel in a 10% sulfuric acid environment, and the higher peel strength indicates that the composite coating on the steel surface constructs a chemical-physical bonding interface at the steel-plastic interface.

[0118] From the data of Example 2 and Comparative Example 1 in Table 1, it can be seen that the lack of the first impregnation solution leads to a decrease in ring stiffness, which is due to the fact that the initial passivation layer formed by the sodium silicate / zinc sulfate system can effectively improve the load resistance of the pipe. The content of free hydroxyl groups on the surface of the steel strip is relatively low, which reduces the effective anchoring points of the silane coupling agent and reduces the peel strength. The shortened creep rupture time indicates that an effective stress buffer layer has not been formed, and the stress concentration at the metal-plastic interface has intensified. The higher mass change rate indicates that after the silicate protective layer is missing, the steel substrate is easily exposed to the corrosive environment, and the continuous dissolution of iron ions accelerates the interface degradation.

[0119] From the data of Example 2 and Comparative Example 2 in Table 1, it can be seen that the peel strength is reduced without the second immersion treatment, which proves that the treatment of silane coupling agent is crucial to interface strengthening. The shortened creep time reflects that the molecular-level interface bonding is not formed, resulting in a decrease in stress transfer efficiency. The increased mass change rate indicates that the absence of silane film causes microchannels to exist between the epoxy resin coating and the steel substrate, H +Ions penetrate through interface defects and cause local corrosion. The decrease in ring stiffness indicates that poor interface bonding leads to a decrease in the steel-plastic synergistic load-bearing capacity.

[0120] From the data of Example 2 and Comparative Example 3 in Table 1, it can be seen that the peel strength dropped sharply without epoxy resin coating, proving that the epoxy coating modified by nano-silica sol is the main load-bearing layer. The shortened creep time shows that the absence of coating makes the steel strip directly bear the creep stress. The extremely high mass change rate exposes the instability of the unprotected modified layer in an acidic environment, and the silicate film layer undergoes hydrolysis reaction during long-term immersion. The deterioration of water pressure resistance shows that the epoxy resin network plays a key role in sealing microscopic pores.

[0121] It can be seen from the data of Example 2 and Comparative Example 4 in Table 1 that the order of the steel strip surface treatment process is crucial to the performance of the drainage pipe. First, surface defects are eliminated through silicate passivation, then molecular bridges are established through silane coupling, and finally mechanical interlocking is achieved with a nano-composite coating. The synergistic effect of "chemical anchoring-physical enhancement" greatly improves the overall performance of the product.

[0122] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above. For the sake of simplicity, they do not provide test basis standards in the details.

Claims

1. A hollow wall plastic steel winding drainage pipe, characterized in that: From inside to outside, it includes: a wound inner tube, a steel belt wound layer and an outer tube; The steel strip winding layer is obtained by winding a pre-treated steel strip around the surface of the winding inner tube; The preparation steps of the pretreated steel strip are as follows: S1: adding sodium silicate, zinc sulfate, sodium potassium tartrate and sodium dodecylbenzene sulfonate into deionized water, stirring for 20-40 minutes, and adjusting the pH to 3.5-4 with nitric acid to obtain a first impregnation solution; S2: adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, glacial acetic acid and ethanol into deionized water and stirring for 20-40 minutes to obtain a second impregnation solution; S3: immersing the steel strip in the first impregnation liquid, controlling the temperature of the first impregnation liquid to be 55-65° C., the immersion time to be 8-12 min, and then drying at 75-85° C. for 10-20 h to obtain a primary modified steel strip; S4: Immersing the primary modified steel strip in a second impregnation liquid, controlling the temperature of the second impregnation liquid to be 20-30° C., the impregnation time to be 25-35 seconds, then standing in an environment with a humidity of 55%-65% for 10-20 minutes, and then curing at 105-115° C. for 15-25 minutes to obtain a secondary modified steel strip; S5: adding epoxy resin E-44, nano silica sol and polyamide curing agent into a xylene / n-butanol mixed solvent, stirring for 20-40 minutes to obtain an epoxy resin coating, and then coating the epoxy resin coating on the surface of the secondary modified steel strip by a reverse roller coating process, controlling the wet film thickness to 80-90 μm, and then curing at 75-85° C. for 6-10 minutes, 120-140° C. for 12-18 minutes, and 95-105° C. for 8-12 minutes in sequence to obtain a pretreated steel strip; In step S1, the weight ratio of sodium silicate, zinc sulfate, sodium potassium tartrate, sodium dodecylbenzene sulfonate and deionized water is 10-14:4-5:1-3:0.1-0.15:80-120; In step S2, the weight ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, glacial acetic acid, ethanol and deionized water is 8-12:0.3-0.6:8-12:50-70; In the step S5, the weight ratio of epoxy resin E-44, nano silica sol, polyamide curing agent and xylene / n-butanol mixed solvent is 80-120:20-40:30-40:100-140.

2. The hollow wall plastic-steel wound drainage pipe according to claim 1 is characterized in that: The preparation method of the winding inner tube is as follows: high-density polyethylene, pentaerythritol stearate and an antioxidant are melt-extruded at 210-220° C. through a twin-screw extruder, and an inner tube blank with a wall thickness of 3.5-4.0 mm and an outer diameter of 700-800 mm is formed through an annular die head, and the inner tube is cut after water cooling and shaping to obtain an inner tube; the inner tube is placed on a winding machine, the winding angle is adjusted to 45 degrees, the winding machine is started, and the winding speed is set to 0.5-2 m / min. During the winding process, hot air is used to fuse and connect the wound pipes during the winding process to obtain a wound inner tube.

3. The hollow wall plastic-steel wound drainage pipe according to claim 2 is characterized in that: The weight ratio of the high-density polyethylene, high-density polyethylene and antioxidant is 75-85:2-4:0.1-1.

4. The hollow wall plastic-steel wound drainage pipe according to claim 2 is characterized in that: The high-density polyethylene has a melt index of 0.3-0.5 g / 10 min at 190° C. and 2.16 kg.

5. The hollow wall plastic-steel wound drainage pipe according to claim 1 is characterized in that: In step S3, the steel strip is a Q235 steel strip with a thickness of 0.4-0.6 mm.

6. The hollow wall plastic-steel wound drainage pipe according to claim 1 is characterized in that: The amine value of the polyamide curing agent in step S5 is 240 mgKOH / g.

7. The hollow wall plastic-steel wound drainage pipe according to claim 1 is characterized in that: The SiO2 content in the nano-silica sol in step S5 is 30wt% and the particle size is 20nm.

8. The hollow wall plastic-steel wound drainage pipe according to claim 1 is characterized in that: In the step S5, the volume ratio of xylene to n-butanol in the xylene / n-butanol mixed solvent is 7:

3.

9. A method for manufacturing a hollow wall plastic-steel wound drainage pipe according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Wrap the pretreated steel strip around the outer wall of the winding inner tube, set the winding angle to 30 degrees, start the winding machine, set the winding speed to 0.4-0.6 m / min, and wind 3 turns to obtain a steel strip wound tube; (2) High-density polyethylene, pentaerythritol stearate and antioxidant are melt-extruded at 210-225° C. through a twin-screw extruder, and the extrudate is wrapped on the outer surface of the steel strip winding pipe with a wrapping thickness of 1.8-2.2 mm. The pipe is then cooled and cut to obtain a hollow-wall plastic-steel winding drainage pipe.

10. The method for manufacturing the hollow wall plastic-steel wound drainage pipe according to claim 9, characterized in that: In the step (2), the weight ratio of high-density polyethylene, pentaerythritol stearate and antioxidant is 75-85:2-4:0.1-1, and the melt index of high-density polyethylene is 0.08-0.15 g / 10 min at 190° C. and 2.16 kg.